Converging towards Euroscepticism? Negativity in news coverage during the 2014 European Parliament elections in Germany and the UK. Issue 3 (27th May 2019) - Galpin, Charlotte; Trenz, Hans-Jörg
ABSTRACT: In the run up to the 2014 European Parliament elections, the new Spitzenkandidaten process and European-wide party campaigns were considered a mechanism to create a more engaged European public. However, right-wing Eurosceptic party groupings gained a significant minority of the seats in the 2014 EP elections. We place this in the context of media and public sphere dynamics of politicised EP elections that have given selective salience to Euroscepticism. We discuss two interrelated media biases that explain this convergence of public debates towards Euroscepticism: a media negativity bias in the selection and tonality of EU news and a media polity bias that privileges contestation of the constitutional make-up of the EU over political and policy-based debates. To investigate these media biases empirically, we analyse EP election news during the 2014 European Parliament elections, taking Germany and the UK as ideal-type cases. We find that the UK news demonstrates a strong negative bias towards the EU polity, whereas in Germany EP debates focus more strongly on EU politics and policies and in fact demonstrate a positivity bias with regard to assessments of the legitimacy of the EU polity.